Media and development - Scott, Martin, 1982- (London Zed books, 2014)
The media have a vital role to play in all aspects of development. The significance of media for development is not limited to either communicating development messages or to facilitating people's participation in defining and implementing their own development. Media and Developmentargues that media can play a myriad of roles in influencing levels of charitable donations and the public policies of donor countries, reinforcing or challenging global power relations between the North and South, as well as promoting, or otherwise, good governance, democracy, and human rights. This book provides a critical, interdisciplinary introduction to the relationship between media and development. It is unique in focusing not just on the subject of development communication, but also on media development and media representations of development and of developing countries.
Includes bibliographical references (pages 205-222) and index.
Keywords: Mass media; Mass media -- Economic aspects; Mass media -- Social aspects; Economic development; Economic development; Mass media; Mass media -- Economic aspects; Mass media -- Social aspects